Análise do desempenho de substratos da agropecuária na produção de biogás - Krieger, Pedro Augusto (2019)
Fuel production from animal waste can be an attractive option to reduce greenhouse gas (GHG) emissions. Biogas produced by anaerobic decomposition of animal waste is a renewable energy source that has great potential for expansion in the energy grid in places where the main economic activity is agriculture, such as the western region of Paraná State. The biogas production potential, as a function of the waste volume, provides the biochemical production capacity of biogas by mixing different substrates and is fundamental to evaluate the technical viability of this treatment technology. The present work aims to evaluate the potential of methanogenic production of different residues of a biogas desulphurization agricultural property through microbiological filtration. The residues were fractionated into 7 groups, each made in quadruplicates: Inoculum; Inoculum + Cellulose; Inoculum + Serum; Inoculum + Cattle; Inoculum + Swine; Inoculum + Swine + Serum; Inoculum + Swine + Cattle, totaling 28 reactors. At the end of the incubation period, 58 days, it can be seen that the Swine + Serum substrate reached the highest level of biogas production compared to the other substrates, reaching a volume of 1693,58 mLN gSV-1.